Do Young Children's Representations of Discipline and Empathy Moderate the Effects of Punishment on Emotion Regulation?. Issue 1 (7th July 2015) - Lee, Young‐Eun; Brophy‐Herb, Holly E.; Vallotton, Claire D.; Griffore, Robert J.; Carlson, John S.; Robinson, JoAnn L.
Abstract: This study examined whether children's representations of parenting (perceptions of authoritative discipline and empathy) moderated the association between harsh punishment—including corporal punishment (CP) and verbal punishment (VP)—and children's emotion regulation at the age of five years. Participants were 559 low‐income mother‐child dyads. Maternal self‐reports and home observations were used to measure punishment. Children's representations were assessed using the MacArthur Story Stem Battery. Children's emotion regulation was assessed by observer rating via the Leiter International Performance Scale–Revised. Hierarchical multiple regressions revealed that children's authoritative disciplinary representations moderated the effects of both VP and CP on children's emotion regulation. Empathic representations moderated the effects of VP only on children's emotion regulation. The current findings highlight the role of children's internal representations as potential protective factors in the context of harsher forms of punishment.